UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS TENAGA PENDIDIK DI SD IMAM NAWAWI SCHOOL BOGOR - Carles Ritonga (UNISAN JURNAL, 2024)
This research aims to investigate the school principal's efforts to improve the quality of teaching staff at Imam Nawawi School Bogor Elementary School. In the educational context, the role of the principal has a significant impact on the quality of teaching and learning in schools. The research method used is qualitative with data collection techniques through in-depth interviews, observation and documentation studies. The research results show that the principal at SD Imam Nawawi School Bogor has implemented various strategies to improve the quality of teaching staff, including training and professional development, performance monitoring, coaching, and creating a conducive work environment. In addition, supporting factors and obstacles in implementing these efforts were also identified. The implications of this research underline the important role of school principals in improving the quality of teaching staff as a key factor in improving the quality of education in elementary schools. Keywords: School Principals and Quality of Teaching Personnel